The Attitude of Nurses in Hospitals of Kermanshah towards Safety climate - Hamed Yarmohammadi; Younes Sohrabi; Hosain Salimi; Arman Mohammadi; Ehsan Mohammadi (Shahid Sadoughi University of Medical Sciences, 2020)
Introduction: Safety climate is defined as the employees' common insights about safety management in a specific place and time. Nurses have a highly risky occupation, in which they are required to take safety issues into consideration. This study aimed at investigating the attitude of nurses towards safety climate in the hospitals of Kermanshah City, Iran. Methods: This descriptive-analytical research was conducted with 112 nurses in the hospitals of Kermanshah City. A two-section questionnaire was administered for data collection. The first part was related to the nurses' demographic and occupational characteristics and the second part contained the nurses' safety climate questionnaire. After data collection, the data were analyzed by SPSS-16. Results: Results showed that the mean and standard deviation of the safety climate in nurses was 0.56 ± 3.06. A significant relationship was found between all factors, except for the relationship between cumulative burnout and error reporting. The safety climate was almost equal between men and women. Moreover, safety climate was higher in single people than the married ones. In the morning shift, the highest safety climate was in the workplace. Furthermore, people with a second job felt safety climate more. Conclusion: Research results showed that safety climate was not at a satisfactory level in the studied nursing personnel. Therefore, it is suggested to improve the safety climate and its effects on the safety performance by training safety issues, holding technical courses on safety, and adjusting work-rest time.